Begonia trevisoensis, a new species of Begonia sect. Pritzelia (Begoniaceae) from Santa Catarina State, Brazil - Jaramillo, Julio C.; Kollmann, Ludovic Jean Charles; Fiaschi, Pedro (Phytotaxa, 2018)
A new species of Begonia is documented from Santa Catarina state, Brazil. Begonia trevisoensis is so far known only from the municipality of Treviso, in the Southern part of Santa Catarina. The new species is similar to B. itatinensis, from which it can be distinguished by the leaf and stipule size and form. A detailed morphological description, line drawings, photographs, map, comparisons with morphologically similar species, conservation status and a discussion of the species sectional placement are provided.